PENGARUH DISIPLIN KERJA TERHADAP KUALITAS PELAYANAN APARAT PADA KANTOR DESA TONRALIPUE KECAMATAN TANASITOLO KABUPATEN WAJO - Eka Patmasari; Supris Musiafir; Sulhayati Sulhayati (Universitas Mbojo Bima, 2023)
This study aims to determine; (1) the work discipline of the apparatus at the Tonralipue Village Office, Tanasitolo District, Wajo Regency; (2) Service quality at the Tonrlipue Village Office, Tanasitolo District, Wajo Regency; (3) The effect of work discipline on the quality of service for officers at the Tonralipue Village Office, Tanasitolo District, Wajo Regency. For this reason, collecting and information was carried out by direct observation [observation]. The subjects in this study were people who had interests at the Tonralipue Village Office and a sample of 26 people was taken, and looking for supporting data in the form of official documents. The research data was processed by calculating the percentage value of the answers submitted by respondents to the research questionnaire, both questionnaires regarding work discipline on service quality. And to determine the effect of work discipline on the quality of employee service, both separately and collectively, calculations were made on the correlation and linear regression values of the research variables. The results of the study show that the discipline applied by the village head is that work discipline has been carried out with very good quality. This shows that the results of the management of inferential statistics reveal that work discipline has a positive effect on the quality of apparatus service. On the basis of the results of this study, it is suggested to the Village and Officers of the Tonralipue village office, Tanasitolo sub-district, Wajo district, to try to maintain the quality of work discipline and the quality of service for officials that have been realized at this time, and even try to increase it even more in the future because it has proven to have a positive impact on apparatus work discipline.